The Influence of Motivational Factors on Work Performance of Pencak Silat Athletes at SEA Games (Universitas Negeri Semarang, 2022)
Pencak Silat has been patented as an Indonesian Tradition by UNESCO (UNESCO, 2019). Pencak Silat always occupy top three positions in the multi-sport event South East Asian (SEA) Games. SEA Games at 2017 the Indonesian Pencak Silat contingent won 3rd place overall, while in 2019 the Indonesian Pencak Silat contingent won 1st position. The objectives of this study are (1) to analyze the perceptions of Pencak Silat athletes at the 2017 SEA Games and 2019 SEA Games, regarding motivational factors and job perfomance (2) to know the influence of motivation on job performance of SEA Games Pencak Silat Athletes. Sampling method used was purposive sampling. The analytical tools used were descriptive analysis and multiple linear regression. Based on the results, the SEA Games pencak silat athletes of 2017 and 2019 were motivated to improve job performance. The motivational factor Need for Achievement is most significant and positive which means, if athletes are given the opportunity to increase creativity, and enthusiasm for achievement it will increase job performance variable.